Análise de crescimento de batata, cv. Baronesa, transformada com gene de resistência ao PVY - Pohl, Simone (2008)
Potato ( Solanum tuberosum L.), even though it is one of the main crops produced worldwide, breeding programs ar difficult and require a great deal of time and energy. Recombinant DNA technology with its potential capacity of isolating and transferring genes from any organism, allows incorporating in plants new characters of agricultural interest. However, consequences of the incorporation of determined genes on physiological characteristics are sometimes unknown. The aim of this study was to evaluate growth characteristics, partition of assimilates, morphological atributes and components of the production of potato plants genetically modified with resistance genes to PVY virus, during the plant life cycle. For this, potato tuber of Baronesa cultivar and their respective transformed genotype were planted in pots and kept in greenhouse for 84 days. The transformation of Baronesa cultivar with virus resistant genes also did not alter the majority of the evaluated growth characteristics.